EFISIENSI PEMASARAN BUAH JAMBLANG (Syzygium cumini (L) Skeels) (STUDI KASUS DI DESA TRIWIDADI, KECAMATAN PAJANGAN, KABUPATEN BANTUL, PROVINSI YOGYAKARTA) - Soleh Mulyana; Suhartono Suhartono; Aris Sudomo (Jurnal Agroforestri Indonesia, 2019)
Jamblang is one of multipurpose tree species especially utilised for medical purposes. However, population of jamblang tree on private land in Bantul district is still limited because of less information on jamblang’s advantage value and its silvicultural technique. The objective of the research is to find out the marketing flow and the efficiency  of  jamblang fruit in Triwidadi Village, Pajangan Sub District, Bantul District of Yogyakarta. The Data was collected by interviewing 15 farmers who owned jamblang trees, 1distributor and 1 retailer using snowball method. The research shows that marketing flow of jamblang should contain several marketing institutions i.e : producer/farmers, collector, retailer and customer  through 3 models of marketing flow. In first model of marketing flow, farmers sell un-harvested jamblang fruit (still on the tree) to the collectors, then the collectors sell it to the retailer and the retailer sell it to the customer. In the second method, farmers sell the harvested jamblang fruit to the collectors to be continued to the retailer and then the customer. Meanwhile, in the third marketing flow, farmers sell the harvested jamblang fruit directly to the retailer to be continued  to the last customers. Marketing system of jamblang throughsecond and third method is more efficient then the first marketing because the methods have lower margin (Rp 2500 /kg) and farmer’s share more than 50% (58.33%).